Transport and retention of carbon dots (CDs) in saturated and unsaturated porous media: Role of ionic strength, pH, and collector grain size - Kamrani, Salahaddin; Rezaei, Mohsen; Kord, Mehdi; Baalousha, Mohammed (Water research (Oxford), 2018)
Carbon-based engineered nanoparticles (ENPs) are widely used in consumer products due to their small size and unique physicochemical properties. Therefore, their release and distribution into the surface and subsurface environment is a subject of concern. Several studies have evaluated the transport and retention of carbon nanotubes and fullerenes, but none investigated the transport and retention of carbon dots (CDs). The aim of this research is to fill this knowledge gap by evaluating the transport and retention of CDs in saturated and unsaturated porous medium. Here, we investigate the effects of solution ionic strength (IS, 1–700 mM NaCl) and pH (4–9), the initial concentration of CDs (50–200 mg L−1), and porous media grain size (0.20–0.50 mm, 0.50–1 mm, 1–1.5 mm and 1.5–2 mm grain diameters) on the transport and retention of CDs in saturated (upward flow) and unsaturated (downward flow) quartz porous media. A mathematical model based on the advection-dispersion equation coupled with the second-order kinetics was used to fit the breakthrough curves and to calculate the attachment and straining rates under the different experimental conditions. These analyses were underpinned by characterization of CD surface functional groups, surface charge and aggregation under the different experimental conditions, calculation of CD-CD and CD-quartz sand interaction potential according to DLVO theory. Transport and retention of CDs in quartz porous media are consistent with those observed for other types of carbon-based ENPs such as fullerenes and carbon nanotubes. Mobility of CDs in both saturated and unsaturated porous media increases with the decrease in ionic strength, increase in pH, and increase in collector grain size. Retention of CDs increases with the increase in IS, decrease in pH and decrease in grain size. Generally, CDs mobility was higher under saturated than under unsaturated flow conditions, for the same experimental conditions. Overall, CDs tend to be highly mobile and could travel for long distances at a wide range of environmental conditions. [Display omitted] •Carbon Dots displays high mobility within saturated and unsaturated sand packs.•DLVO theory can explain the observed trends in the mobility of CD within porous media.•CD solution properties has high effects on CD immobilization.•CD mobility is higher under saturated than under unsaturated flow conditions.